Bibliometric Review to Explore Emerging High-Intensity Interval Training in Health Promotion: A New Century Picture - You, Yanwei; Li, Wenkai; Liu, Jianxiu; Li, Xingtian; Fu, Yingyao; Ma, Xindong (Frontiers in Public Health, 2021)
Background: High-intensity interval training (HIIT) is an emerging exercise strategy and is considered to be a recipe for health promotion. This study aimed to systematically identify collaboration networks, track research trends, highlight current hotspots, and predict future frontiers in HIIT and its applications in health promotion since the start of the new century. Methods: Relevant original publications were obtained from the Science Citation Index Expanded of the Web of Science Core Collection (WoSCC) database between 2001 and 2020. CiteSpace and VOSviewer software were used to perform bibliometric visualization and comparative analysis of involved indexes that included countries, institutions, journals, authors, references, and keywords. Results: A total of 572 papers were included, and the trend of annual publications showed a remarkable growth. The United States and the University of Exeter were the most productive country and institutions, respectively, with 107 and 18 publications, respectively. European Journal of Applied Physiology took the lead in the number of published articles, and Medicine and Science in Sports and Exercise ranked first in the cocitation counts. Barker AR and Gibala MJ were considered as the most productive and the most highly-cited authors. Conclusions: “Health risks,” “adolescent,” and “aging” are the three noteworthy topics during the evolution of HIIT-health promotion (HIIT-HP) research. The current research hotspots of HIIT and its practices in the health promotion domain lies in “metabolic diseases,” “cardiovascular diseases,” “neurological diseases,” and “musculoskeletal diseases.” The authors summarize that “prevention and rehabilitation,” “micro and molecular level,” and “cognition and mental health” are becoming frontiers and focus on the health topics related to HIIT in the upcoming years, which are worthy of further exploration.